Chemical speciation of soil solution to assess calcium and aluminum uptake by coffe roots - Chaves, Júlio C. D.; Pavan, Marcos A.; Miyazawa, Mário (Pesquisa Agropecuaria Brasileira, 1991)
A greenhouse experiment was conducted with two acid soils to study Ca and Al uptake by coffee roots using the following salts: CaCO3, CaCl2, Ca(NO3)2, CaSO4, and MgCO3. Saturation extracts of the soil samples were analyzed for all major cations and anions to have input data for chemically speciating Al and Ca in the soil solution phase using a computer program GEOCHEM. All Casalts increased the concentration of total Cat in solution. CaCO3 increased the concentration of Ca2+ and neutralized Al3+. CaCl2 and Ca(NO3)2 increased the concentration of Al3+ and decreased Ca2+ in relation to CaCO3. No significant ionic complexation of Cl- and NO3- with Al was computed, but some with Ca as CaCl+ and CaNO3+. Gypsum resulted in SO42- ion-pairing with Al and Ca to form AlSO4+, and CaSO4o, thereby decreasing Al3+ and Ca2+ in soil solution. Coffee dry matter increased with increasing Ca2+ and decreasing Al3+ in soil solution. The Ca uptake by roots decreased by lowering the valence of Ca in soil solution through complex formations: Ca2+ > CaNO3+≥ CaCl+ > CaSO4o.